TREATMENT OF CHRONIC TONSILLITIS WITH THYMOGEN SPRAY - Khodjanov Shokhimardon Khodjanovich; Djuraev Jamolbek Abdukaharovich; Soatov Ilyasjon Olim ogli; Shaumarov Azizkhon Zavkievich; Makhamadaminova Shaira Abduvalievna (Web of Journals Publishing, 2024)
During the study, 30 patients and 30 volunteer workers were selected for the control group, who applied to the ENT polyclinic of the Tashkent Medical Academy . The diagnosis of the disease is based on general and local symptoms, patient complaints, medical history, and results of laboratory tests. Pathological microflora were found in the obtained smears. Improvement of treatment methods for chronic tonsillitis was developed.
Keywords: Chronic tonsillitis, chronic pharyngitis, lacunae, lymphocyte.